Glass fiber reinforced high-viscosity medical composite material and preparation method thereof

By adding degradable glass fibers and other reinforcement materials to medical biodegradable materials, the ratio and preparation process are optimized, and the viscosity of the material is reduced during the thermal processing process is solved, and the high thermal stability and mechanical properties of the material are achieved, which is suitable for orthopedic restoration applications.

CN119701086APending Publication Date: 2025-03-28北京纳通医学研究院有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411881765.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Medical biodegradable materials are easily affected by thermal effects during thermal processing, resulting in a decrease in molecular weight and viscosity, affecting their degradation cycle and mechanical properties in the human body.

Method used

Using glass fiber reinforced high viscosity medical composite materials, the thermal stability and mechanical properties of the material are improved by adding degradable glass fibers, reinforcement materials and processing aids to the matrix polymer.

Benefits of technology

It significantly improves the thermal stability, strength and rigidity of composite materials, ensures that high viscosity and molecular weight are maintained during the thermal processing process, and stabilizes the degradation cycle and mechanical properties in the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198371260000191
    Figure BDA0005198371260000191
Patent Text Reader

Abstract

The invention relates to the technical field of biomedical composite materials, and particularly discloses a glass fiber reinforced high-viscosity medical composite material and a preparation method thereof. The composite material comprises the following components in parts by weight: 100 parts of a matrix polymer, 10-20 parts of degradable glass fibers, 10-20 parts of a reinforcing material and 2-5 parts of a processing aid, the preparation method of the composite material comprises the following steps: uniformly blending the matrix polymer, the reinforcing material and the processing aid through a high-speed mixer to obtain a mixture; adding the mixture into an extruder through a feeding machine, adding degradable glass fibers into a fiber adding opening after melt is extruded out of an opening mold, introducing a special thread element combination, and extruding and granulating to obtain the required glass fiber reinforced high-viscosity medical composite material. The obtained composite material can keep high viscosity and molecular weight in the hot working process, and the degradation period and mechanical performance stability in a human body are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical composite materials, and more specifically, to a glass fiber reinforced high-viscosity medical composite material and a preparation method thereof. Background Art

[0002] With the continuous advancement of medical technology, orthopedic implant medical devices have gradually entered the era of biodegradable materials. In the research of biodegradable orthopedic repair materials, self-reinforced biodegradable composite materials such as polylactic acid (PLA), polyglycolic acid (PGA) and their copolymers such as PGA / PLLA are currently hot topics. The above self-reinforced biodegradable composite materials have gradually been used in clinical practice due to their excellent biocompatibility and biodegradability, especially in the field of orthopedic repair, showing significant advantages.

[0003] Traditional bone repair surgery usually uses metal or other non-degradable materials, which have poor biocompatibility with the human body and often require secondary surgery to remove after healing. This not only increases the patient's pain and surgical risks, but also increases medical costs. Compared with traditional repair materials, biodegradable materials can degrade in the human body by themselves, avoiding the harm caused by secondary surgery to the human body, while also being able to inhibit local inflammation, safe and reliable.

[0004] However, biodegradable materials are easily affected by thermal effects during processing, especially during the thermal processing stage, which leads to a decrease in the molecular weight and viscosity of the materials, thereby affecting their degradation cycle and mechanical properties in the human body. At present, there is a lack of clear solutions for the processing technology of medical biodegradable materials on the market. However, the existing industrial biodegradable material process methods are not completely applicable to medical biodegradable materials. For example, the process methods introduced in patent announcement numbers CN115157478B and CN116277593B are mainly aimed at industrial biodegradable materials. If they are directly used for the processing of medical biodegradable materials, it will lead to excessive carrying capacity of the processing equipment, excessive loss of equipment due to long-term operation, and shortening the service life of the equipment. Based on the above statements, the present invention proposes a glass fiber reinforced high-viscosity medical composite material and a preparation method thereof. Summary of the invention

[0005] In order to solve the problem that current medical biodegradable materials are easily affected by thermal effects during processing, especially in the thermal processing stage, resulting in a decrease in the molecular weight and viscosity of the materials, thereby affecting their degradation cycle and mechanical properties in the human body, the present invention provides a glass fiber reinforced high-viscosity medical composite material and a preparation method thereof.

[0006] In the first aspect, the present invention provides a glass fiber reinforced high-viscosity medical composite material, which adopts the following technical solution:

[0007] A glass fiber reinforced high-viscosity medical composite material comprises the following raw materials in parts by weight: 100 parts of a matrix polymer, 10-20 parts of degradable glass fibers, 6-10 parts of a reinforcing material, and 2-5 parts of a processing aid.

[0008] Preferably, the glass fiber reinforced high-viscosity medical composite material comprises the following raw materials in parts by weight: 100 parts of matrix polymer, 12-18 parts of degradable glass fiber, 7-9 parts of reinforcing material, and 3-4 parts of processing aid.

[0009] Preferably, the glass fiber reinforced high-viscosity medical composite material comprises the following raw materials in parts by weight: 100 parts of matrix polymer, 15 parts of degradable glass fiber, 8 parts of reinforcing material, and 3.5 parts of processing aid.

[0010] Preferably, the matrix polymer comprises polylactic acid, polyglycolic acid and polybutylene succinate in a mass ratio of 4-5:2-3:1.

[0011] Preferably, the degradable glass fiber is prepared by the following method:

[0012] A1. Add silicon dioxide, calcium carbonate, calcium oxide, calcium phosphate, magnesium oxide and boron oxide into a ball mill, and mix them evenly to obtain a mixed powder;

[0013] A2. Place the mixed powder in a high temperature furnace, heat until completely melted, and keep the temperature to obtain a uniform glass melt;

[0014] A3, drawing the glass melt through a glass fiber drawing machine, annealing the drawn fiber filaments and then cooling them to obtain glass fiber filaments;

[0015] A4. Coat the polymer solution onto the surface of the glass fiber, dry it, and cut it to obtain the degradable glass fiber.

[0016] Preferably, the weight parts of the raw materials in step A1 are as follows: 40-50 weight parts of silicon dioxide, 20-30 weight parts of calcium carbonate, 5-15 weight parts of calcium oxide, 5-10 weight parts of calcium phosphate, 5-10 weight parts of magnesium oxide, and 5-10 weight parts of boron oxide.

[0017] Preferably, the polymer solution in step A4 is prepared by the following method:

[0018] Caprolactone monomer, vanillic acid, syringic acid and catalyst in a mass ratio of 10-15:1-2:1:0.1-0.3 are added to chloroform, and after being fully mixed, the reaction system is heated to 100-140° C. under nitrogen protection, and the polymerization reaction is carried out for 4-8 hours to obtain a polymer solution.

[0019] Preferably, the catalyst is stannous isooctanoate.

[0020] Preferably, the reinforcing material is hydroxyapatite nanoparticles.

[0021] Preferably, the processing aid comprises polyethylene glycol and hydrogenated castor oil in a mass ratio of 2-5:1-3.

[0022] In a second aspect, the present invention provides a method for preparing a glass fiber reinforced high-viscosity medical composite material, which adopts the following technical solution:

[0023] A method for preparing a glass fiber reinforced high-viscosity medical composite material comprises the following steps:

[0024] S1. Weigh the base polymer, degradable glass fiber, reinforcing material and processing aid according to weight for later use;

[0025] S2, blending the base polymer, the reinforcing material and the processing aid uniformly by a high-speed mixer to obtain a mixture;

[0026] S3. Add the mixed material into the extruder through a feeder. After the melt is extruded through the die, add degradable glass fiber at the fiber adding port. At the same time, introduce a special screw component combination, extrude and granulate, and obtain the required glass fiber reinforced high-viscosity medical composite material.

[0027] Preferably, in step S3, the extruder temperature is 150-190° C., the feeding frequency is 3-8 Hz, and the feeding speed is 40-80 rpm.

[0028] Preferably, in the special thread element combination in step S3, the element types are: ZME, chamfer, rotor, hexagonal prism, slotted element, TKR, TKL, ordinary three-head, eccentric three-head, ordinary four-head, and four-prism.

[0029] In summary, the present invention has the following beneficial effects:

[0030] 1. The present invention adopts polylactic acid, polyglycolic acid and polybutylene succinate as matrix polymers, and prepares a glass fiber reinforced high-viscosity medical composite material by adding degradable glass fiber, reinforcing material and processing aid. By optimizing the combination ratio of the matrix polymer, the degradation rate and mechanical properties of the composite material can be effectively controlled. The addition of degradable glass fiber significantly improves the thermal stability, strength and rigidity of the composite material, so that it performs better when subjected to mechanical stress in orthopedic repair applications; the composite material obtained by the present invention can maintain a high viscosity and molecular weight during thermal processing, ensuring the stability of the degradation cycle and mechanical properties in the human body.

[0031] 2. The present invention uses silicon dioxide, calcium carbonate, calcium oxide, calcium phosphate, magnesium oxide and boron oxide as raw materials. The degradable glass fiber made from the above mineral raw materials can significantly improve the thermal stability, strength and rigidity of the composite material; and can achieve gradual degradation and release of beneficial ions while providing the necessary biocompatibility; by coating the surface of the glass fiber with a polymer solution, on the one hand, it can effectively improve the interface bonding between the degradable glass fiber and the polymer matrix and enhance the overall mechanical properties of the composite material; on the other hand, the flexibility, antibacterial and antioxidant properties of the polymer solution help to further improve the comprehensive performance of the composite material.

[0032] 3. The present invention uses caprolactone monomer, vanillic acid and syringic acid to polymerize under the action of a catalyst to form a polymer solution. The cross-linked network structure formed in the polymer solution limits the movement of the polymer chain, thereby improving the heat resistance and mechanical properties of the composite material. Vanillic acid and syringic acid have natural antibacterial and antioxidant properties, which help to improve the anti-infection ability of the composite material. The phenolic hydroxyl groups and other groups contained in their molecular structures have good free radical capture capabilities, which can increase the interaction between molecules and further improve the thermal stability of the composite material.

[0033] 4. The present invention uses polyethylene glycol and hydrogenated castor oil as processing aids, which can reduce the internal friction of the material during processing, improve melt fluidity, and reduce processing energy consumption on the one hand, and increase the flexibility of the polymer, improve impact resistance, and make the composite material less likely to break during use; in addition, hydrogenated castor oil can also improve the stability of the composite material during high-temperature processing, and the processing aid can provide better compatibility between the matrix polymer and other raw materials, making the performance of the composite material more uniform and stable.

[0034] 5. The present invention blends the matrix polymer, reinforcing material and processing aid and adds them to the extruder through a feeder. After the melt is extruded through the die, degradable glass fiber is added to the fiber adding port, and a special thread element combination is introduced. The glass fiber reinforced high-viscosity medical composite material is obtained by extrusion granulation. The preparation method of the present invention is simple and adopts a special thread combination, which can further reduce the thermal degradation of the composite material and improve the distribution and dispersion ability of the material. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below with reference to the embodiments.

[0036] Unless otherwise specified, the materials, reagents, etc. used in the present invention can be obtained from commercial sources.

[0037] Among them, the raw materials include:

[0038] Polylactic acid: weight average molecular weight 80,000-300,000, intrinsic viscosity 3.7, purchased from Total Energy Cobien;

[0039] Polyglycolic acid: active ingredient content 99%, CAS No. 26009-03-0, purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.;

[0040] Polybutylene succinate: PBATecoflex C1200, purchased from Shanghai Yilun Plastics Co., Ltd.;

[0041] Caprolactone monomer: ε-caprolactone, product number C109521, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0042] Vanillic acid: Catalog No. V104428, syringic acid: Catalog No. S104156, both purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0043] Stannous 2-ethylhexanoate: Product No. T100108, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0044] Hydroxyapatite nanoparticles: particle size 200 nm, product number HH4250167F1W, purchased from Wuhan Shuer Biotechnology Co., Ltd.;

[0045] Polyethylene glycol: polyethylene glycol 400, product number P432449, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0046] Hydrogenated castor oil: Product No. H196306, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0047] Equipment includes:

[0048] High-speed mixer: specification SHR-25A, purchased from Zhangjiagang Yili Machinery Co., Ltd.;

[0049] Extruder: Thermo Fisher HAAKE micro twin-screw extruder HAAKE process 11;

[0050] Viscometer: Model VISCO-370, Shenzhen Ubola Technology Co., Ltd.

[0051] Embodiments 1-3 provide a glass fiber reinforced high-viscosity medical composite material and a preparation method thereof.

[0052] Example 1

[0053] A glass fiber reinforced high-viscosity medical composite material comprises the following raw materials in parts by weight: 100 parts of a matrix polymer, 10 parts of degradable glass fibers, 6 parts of a reinforcing material, and 2 parts of a processing aid.

[0054] The matrix polymer includes polylactic acid, polyglycolic acid and polybutylene succinate in a mass ratio of 4:2:1; the reinforcing material is hydroxyapatite nanoparticles; and the processing aid includes polyethylene glycol and hydrogenated castor oil in a mass ratio of 2:1.

[0055] Degradable glass fiber is made by the following method:

[0056] A1. Add 40 parts by weight of silicon dioxide, 20 parts by weight of calcium carbonate, 5 parts by weight of calcium oxide, 5 parts by weight of calcium phosphate, 5 parts by weight of magnesium oxide and 5 parts by weight of boron oxide into a ball mill, and mix them evenly by ball milling to obtain a mixed powder;

[0057] A2. Place the mixed powder in a high temperature furnace, heat until completely melted, and keep the temperature for 3 hours to obtain a uniform glass melt;

[0058] A3, drawing the glass melt through a glass fiber drawing machine, controlling the drawing temperature to be 1000°C and the drawing speed to be 300m / min, placing the drawn fiber in an annealing furnace at 400°C for 3h, and cooling to obtain a glass fiber with a diameter of 3μm;

[0059] A4. Coat the polymer solution on the surface of the glass fiber with a coating thickness of 2 μm. Dry at 50° C. for 3 h and cut to obtain 300 tex degradable glass fiber.

[0060] The polymer solution was prepared by the following method:

[0061] Caprolactone monomer, vanillic acid, syringic acid and stannous isooctanoate in a mass ratio of 10:1:1:0.1 were added to chloroform, and after being fully mixed, the reaction system was heated to 100° C. under nitrogen protection and polymerized for 8 hours to obtain a polymer solution.

[0062] A method for preparing a glass fiber reinforced high-viscosity medical composite material comprises the following steps:

[0063] S1. Weigh the base polymer, degradable glass fiber, reinforcing material and processing aid according to weight for later use;

[0064] S2, blending the base polymer, the reinforcing material and the processing aid uniformly by a high-speed mixer to obtain a mixture;

[0065] S3. Add the mixture into an extruder at 150°C through a feeder with a feeding frequency of 3Hz and a feeding speed of 40rpm. After the melt is extruded out of the die, add degradable glass fiber at the fiber adding port, adjust the main engine speed to 240r / min, and introduce a special threaded element combination (element types are: ZME, chamfer, rotor, hexagonal prism, slotted element, TKR, TKL, ordinary three-head, eccentric three-head, ordinary four-head, four-prism), extrude and granulate to obtain the required glass fiber reinforced high-viscosity medical composite material.

[0066] Example 2

[0067] A glass fiber reinforced high-viscosity medical composite material comprises the following raw materials in parts by weight: 100 parts of a matrix polymer, 15 parts of degradable glass fibers, 8 parts of a reinforcing material, and 3.5 parts of a processing aid.

[0068] The matrix polymer includes polylactic acid, polyglycolic acid and polybutylene succinate in a mass ratio of 4.5:2.3:1; the reinforcing material is hydroxyapatite nanoparticles; and the processing aid includes polyethylene glycol and hydrogenated castor oil in a mass ratio of 3.5:2.

[0069] Degradable glass fiber is made by the following method:

[0070] A1, add 45 parts by weight of silicon dioxide, 25 parts by weight of calcium carbonate, 10 parts by weight of calcium oxide, 8 parts by weight of calcium phosphate, 8 parts by weight of magnesium oxide and 8 parts by weight of boron oxide into a ball mill, and mix them evenly by ball milling to obtain a mixed powder;

[0071] A2. Place the mixed powder in a high temperature furnace, heat until completely melted, and keep the temperature for 3 hours to obtain a uniform glass melt;

[0072] A3, drawing the glass melt through a glass fiber drawing machine, controlling the drawing temperature to be 1050°C and the drawing rate to be 400m / min, placing the drawn fiber in an annealing furnace at 500°C for 2.5h, and cooling to obtain a glass fiber with a diameter of 6.5μm;

[0073] A4. Coat the polymer solution on the surface of the glass fiber with a coating thickness of 1 μm. Dry at 60° C. for 2.5 h and cut to obtain 400 tex degradable glass fiber.

[0074] The polymer solution was prepared by the following method:

[0075] Caprolactone monomer, vanillic acid, syringic acid and stannous isooctanoate in a mass ratio of 12.5:1.5:1:0.2 were added to chloroform, and after being fully mixed, the reaction system was heated to 120° C. under nitrogen protection and polymerized for 6 hours to obtain a polymer solution.

[0076] A method for preparing a glass fiber reinforced high-viscosity medical composite material comprises the following steps:

[0077] S1. Weigh the base polymer, degradable glass fiber, reinforcing material and processing aid according to weight for later use;

[0078] S2, blending the base polymer, the reinforcing material and the processing aid uniformly by a high-speed mixer to obtain a mixture;

[0079] S3. Add the mixture into an extruder at 170°C through a feeder with a feeding frequency of 6Hz and a feeding speed of 60rpm. After the melt is extruded out of the die, add degradable glass fiber at the fiber adding port, adjust the main engine speed to 250r / min, and introduce a special threaded element combination (element types are: ZME, chamfer, rotor, hexagonal prism, slotted element, TKR, TKL, ordinary three-head, eccentric three-head, ordinary four-head, four-prism), extrude and granulate to obtain the required glass fiber reinforced high-viscosity medical composite material.

[0080] Example 3

[0081] A glass fiber reinforced high-viscosity medical composite material comprises the following raw materials in parts by weight: 100 parts of a matrix polymer, 20 parts of degradable glass fibers, 10 parts of a reinforcing material, and 5 parts of a processing aid.

[0082] The matrix polymer includes polylactic acid, polyglycolic acid and polybutylene succinate in a mass ratio of 5:3:1; the reinforcing material is hydroxyapatite nanoparticles; and the processing aid includes polyethylene glycol and hydrogenated castor oil in a mass ratio of 5:3.

[0083] Degradable glass fiber is made by the following method:

[0084] A1. Add 50 parts by weight of silicon dioxide, 30 parts by weight of calcium carbonate, 15 parts by weight of calcium oxide, 10 parts by weight of calcium phosphate, 10 parts by weight of magnesium oxide and 10 parts by weight of boron oxide into a ball mill, and mix them evenly by ball milling to obtain a mixed powder;

[0085] A2. Place the mixed powder in a high temperature furnace, heat until completely melted, and keep the temperature for 3 hours to obtain a uniform glass melt;

[0086] A3, drawing the glass melt through a glass fiber drawing machine, controlling the drawing temperature to 1100°C and the drawing speed to 500m / min, placing the drawn fiber in an annealing furnace at 600°C for 2h, and cooling to obtain a glass fiber with a diameter of 10μm;

[0087] A4. Coat the polymer solution on the surface of the glass fiber to a coating thickness of 0.05 μm. Dry at 70° C. for 2 h, and then cut to obtain 500 tex degradable glass fiber.

[0088] The polymer solution was prepared by the following method:

[0089] Caprolactone monomer, vanillic acid, syringic acid and stannous isooctanoate in a mass ratio of 15:2:1:0.3 were added to chloroform, and after being fully mixed, the reaction system was heated to 140° C. under nitrogen protection and polymerized for 4 hours to obtain a polymer solution.

[0090] A method for preparing a glass fiber reinforced high-viscosity medical composite material comprises the following steps:

[0091] S1. Weigh the base polymer, degradable glass fiber, reinforcing material and processing aid according to weight for later use;

[0092] S2, blending the base polymer, the reinforcing material and the processing aid uniformly by a high-speed mixer to obtain a mixture;

[0093] S3. Add the mixture into the extruder at 190°C through a feeder with a feeding frequency of 8Hz and a feeding speed of 80rpm. After the melt is extruded out of the die, add degradable glass fiber at the fiber adding port, adjust the main engine speed to 260r / min, and introduce a special threaded element combination (element types are: ZME, chamfer, rotor, hexagonal prism, slotted element, TKR, TKL, ordinary three-head, eccentric three-head, ordinary four-head, four-prism), extrude and granulate to obtain the required glass fiber reinforced high-viscosity medical composite material.

[0094] In order to verify the performance of the glass fiber reinforced high-viscosity medical composite materials obtained in Examples 1-3 of the present invention, the present invention sets up Comparative Examples 1-5.

[0095] Comparative Example 1

[0096] Comparative Example 1 is different from Example 1 only in that the base polymer is only a single polylactic acid, as follows:

[0097] A glass fiber reinforced high-viscosity medical composite material comprises the following raw materials in parts by weight: 100 parts of a matrix polymer, 10 parts of degradable glass fibers, 6 parts of a reinforcing material, and 2 parts of a processing aid.

[0098] The matrix polymer is polylactic acid; the reinforcing material is hydroxyapatite nanoparticles; and the processing aids include polyethylene glycol and hydrogenated castor oil in a mass ratio of 2:1.

[0099] Degradable glass fiber is made by the following method:

[0100] A1. Add 40 parts by weight of silicon dioxide, 20 parts by weight of calcium carbonate, 5 parts by weight of calcium oxide, 5 parts by weight of calcium phosphate, 5 parts by weight of magnesium oxide and 5 parts by weight of boron oxide into a ball mill, and mix them evenly by ball milling to obtain a mixed powder;

[0101] A2. Place the mixed powder in a high temperature furnace, heat until completely melted, and keep the temperature for 3 hours to obtain a uniform glass melt;

[0102] A3, drawing the glass melt through a glass fiber drawing machine, controlling the drawing temperature to be 1000°C and the drawing speed to be 300m / min, placing the drawn fiber in an annealing furnace at 400°C for 3h, and cooling to obtain a glass fiber with a diameter of 3μm;

[0103] A4. Coat the polymer solution on the surface of the glass fiber with a coating thickness of 2 μm. Dry at 50° C. for 3 h and cut to obtain 300 tex degradable glass fiber.

[0104] The polymer solution was prepared by the following method:

[0105] Caprolactone monomer, vanillic acid, syringic acid and stannous isooctanoate in a mass ratio of 10:1:1:0.1 were added to chloroform, and after being fully mixed, the reaction system was heated to 100° C. under nitrogen protection and polymerized for 8 hours to obtain a polymer solution.

[0106] A method for preparing a glass fiber reinforced high-viscosity medical composite material comprises the following steps:

[0107] S1. Weigh the base polymer, degradable glass fiber, reinforcing material and processing aid according to weight for later use;

[0108] S2, blending the base polymer, the reinforcing material and the processing aid uniformly by a high-speed mixer to obtain a mixture;

[0109] S3. Add the mixture into an extruder at 150°C through a feeder with a feeding frequency of 3Hz and a feeding speed of 40rpm. After the melt is extruded out of the die, add degradable glass fiber at the fiber adding port, adjust the main engine speed to 240r / min, and introduce a special threaded element combination (element types are: ZME, chamfer, rotor, hexagonal prism, slotted element, TKR, TKL, ordinary three-head, eccentric three-head, ordinary four-head, four-prism), extrude and granulate to obtain the required glass fiber reinforced high-viscosity medical composite material.

[0110] Comparative Example 2

[0111] Comparative Example 2 is different from Example 1 only in that the preparation method of the degradable glass fiber is different, as follows:

[0112] A glass fiber reinforced high-viscosity medical composite material comprises the following raw materials in parts by weight: 100 parts of a matrix polymer, 10 parts of degradable glass fibers, 6 parts of a reinforcing material, and 2 parts of a processing aid.

[0113] The matrix polymer includes polylactic acid, polyglycolic acid and polybutylene succinate in a mass ratio of 4:2:1; the reinforcing material is hydroxyapatite nanoparticles; and the processing aid includes polyethylene glycol and hydrogenated castor oil in a mass ratio of 2:1.

[0114] Degradable glass fiber is made by the following method:

[0115] A1. Add 40 parts by weight of silicon dioxide, 20 parts by weight of calcium carbonate, 5 parts by weight of calcium oxide, 5 parts by weight of calcium phosphate, 5 parts by weight of magnesium oxide and 5 parts by weight of boron oxide into a ball mill, and mix them evenly by ball milling to obtain a mixed powder;

[0116] A2. Place the mixed powder in a high temperature furnace, heat until completely melted, and keep the temperature for 3 hours to obtain a uniform glass melt;

[0117] A3, drawing the glass melt through a glass fiber drawing machine, controlling the drawing temperature to be 1000°C and the drawing speed to be 300m / min, placing the drawn fiber in an annealing furnace at 400°C for 3h, and cooling to obtain a glass fiber with a diameter of 3μm;

[0118] A4. Cut the glass fiber filaments to obtain 300tex degradable glass fiber.

[0119] A method for preparing a glass fiber reinforced high-viscosity medical composite material comprises the following steps:

[0120] S1. Weigh the base polymer, degradable glass fiber, reinforcing material and processing aid according to weight for later use;

[0121] S2, blending the base polymer, the reinforcing material and the processing aid uniformly by a high-speed mixer to obtain a mixture;

[0122] S3. Add the mixture into an extruder at 150°C through a feeder with a feeding frequency of 3Hz and a feeding speed of 40rpm. After the melt is extruded out of the die, add degradable glass fiber at the fiber adding port, adjust the main engine speed to 240r / min, and introduce a special threaded element combination (element types are: ZME, chamfer, rotor, hexagonal prism, slotted element, TKR, TKL, ordinary three-head, eccentric three-head, ordinary four-head, four-prism), extrude and granulate to obtain the required glass fiber reinforced high-viscosity medical composite material.

[0123] Comparative Example 3

[0124] Comparative Example 3 is different from Example 1 only in that the preparation method of the degradable glass fiber is different, as follows:

[0125] A glass fiber reinforced high-viscosity medical composite material comprises the following raw materials in parts by weight: 100 parts of a matrix polymer, 10 parts of degradable glass fibers, 6 parts of a reinforcing material, and 2 parts of a processing aid.

[0126] The matrix polymer includes polylactic acid, polyglycolic acid and polybutylene succinate in a mass ratio of 4:2:1; the reinforcing material is hydroxyapatite nanoparticles; and the processing aid includes polyethylene glycol and hydrogenated castor oil in a mass ratio of 2:1.

[0127] Degradable glass fiber is made by the following method:

[0128] A1. Add 40 parts by weight of silicon dioxide, 20 parts by weight of calcium carbonate, 5 parts by weight of calcium oxide, 5 parts by weight of calcium phosphate, 5 parts by weight of magnesium oxide and 5 parts by weight of boron oxide into a ball mill, and mix them evenly by ball milling to obtain a mixed powder;

[0129] A2. Place the mixed powder in a high temperature furnace, heat until completely melted, and keep the temperature for 3 hours to obtain a uniform glass melt;

[0130] A3, drawing the glass melt through a glass fiber drawing machine, controlling the drawing temperature to be 1000°C and the drawing speed to be 300m / min, placing the drawn fiber in an annealing furnace at 400°C for 3h, and cooling to obtain a glass fiber with a diameter of 3μm;

[0131] A4. Coat the polymer solution on the surface of the glass fiber with a coating thickness of 2 μm. Dry at 50° C. for 3 h and cut to obtain 300 tex degradable glass fiber.

[0132] The polymer solution was prepared by the following method:

[0133] Caprolactone monomer, vanillic acid and stannous isooctanoate in a mass ratio of 10:2:0.1 were added to chloroform, and after being fully mixed, the reaction system was heated to 100° C. under nitrogen protection and the polymerization reaction was carried out for 8 hours to obtain a polymer solution.

[0134] A method for preparing a glass fiber reinforced high-viscosity medical composite material comprises the following steps:

[0135] S1. Weigh the base polymer, degradable glass fiber, reinforcing material and processing aid according to weight for later use;

[0136] S2, blending the base polymer, the reinforcing material and the processing aid uniformly by a high-speed mixer to obtain a mixture;

[0137] S3. Add the mixture into an extruder at 150°C through a feeder with a feeding frequency of 3Hz and a feeding speed of 40rpm. After the melt is extruded out of the die, add degradable glass fiber at the fiber adding port, adjust the main engine speed to 240r / min, and introduce a special threaded element combination (element types are: ZME, chamfer, rotor, hexagonal prism, slotted element, TKR, TKL, ordinary three-head, eccentric three-head, ordinary four-head, four-prism), extrude and granulate to obtain the required glass fiber reinforced high-viscosity medical composite material.

[0138] Comparative Example 4

[0139] Comparative Example 4 is different from Example 1 only in that the preparation method of the degradable glass fiber is different, as follows:

[0140] A glass fiber reinforced high-viscosity medical composite material comprises the following raw materials in parts by weight: 100 parts of a matrix polymer, 10 parts of degradable glass fibers, 6 parts of a reinforcing material, and 2 parts of a processing aid.

[0141] The matrix polymer includes polylactic acid, polyglycolic acid and polybutylene succinate in a mass ratio of 4:2:1; the reinforcing material is hydroxyapatite nanoparticles; and the processing aid includes polyethylene glycol and hydrogenated castor oil in a mass ratio of 2:1.

[0142] Degradable glass fiber is made by the following method:

[0143] A1. Add 40 parts by weight of silicon dioxide, 20 parts by weight of calcium carbonate, 5 parts by weight of calcium oxide, 5 parts by weight of calcium phosphate, 5 parts by weight of magnesium oxide and 5 parts by weight of boron oxide into a ball mill, and mix them evenly by ball milling to obtain a mixed powder;

[0144] A2. Place the mixed powder in a high temperature furnace, heat until completely melted, and keep the temperature for 3 hours to obtain a uniform glass melt;

[0145] A3, drawing the glass melt through a glass fiber drawing machine, controlling the drawing temperature to be 1000°C and the drawing speed to be 300m / min, placing the drawn fiber in an annealing furnace at 400°C for 3h, and cooling to obtain a glass fiber with a diameter of 3μm;

[0146] A4. Coat the polymer solution on the surface of the glass fiber with a coating thickness of 2 μm. Dry at 50° C. for 3 h and cut to obtain 300 tex degradable glass fiber.

[0147] The polymer solution was prepared by the following method:

[0148] Caprolactone monomer, syringic acid and stannous isooctanoate in a mass ratio of 10:2:0.1 were added to chloroform, and after being fully mixed, the reaction system was heated to 100° C. under nitrogen protection, and the polymerization reaction was carried out for 8 hours to obtain a polymer solution.

[0149] A method for preparing a glass fiber reinforced high-viscosity medical composite material comprises the following steps:

[0150] S1. Weigh the base polymer, degradable glass fiber, reinforcing material and processing aid according to weight for later use;

[0151] S2, blending the base polymer, the reinforcing material and the processing aid uniformly by a high-speed mixer to obtain a mixture;

[0152] S3. Add the mixture into an extruder at 150°C through a feeder with a feeding frequency of 3Hz and a feeding speed of 40rpm. After the melt is extruded out of the die, add degradable glass fiber at the fiber adding port, adjust the main engine speed to 240r / min, and introduce a special threaded element combination (element types are: ZME, chamfer, rotor, hexagonal prism, slotted element, TKR, TKL, ordinary three-head, eccentric three-head, ordinary four-head, four-prism), extrude and granulate to obtain the required glass fiber reinforced high-viscosity medical composite material.

[0153] Comparative Example 5

[0154] Comparative Example 5 is different from Example 1 only in that no special thread element combination is introduced during the preparation process, as follows:

[0155] A glass fiber reinforced high-viscosity medical composite material comprises the following raw materials in parts by weight: 100 parts of a matrix polymer, 10 parts of degradable glass fibers, 6 parts of a reinforcing material, and 2 parts of a processing aid.

[0156] The matrix polymer includes polylactic acid, polyglycolic acid and polybutylene succinate in a mass ratio of 4:2:1; the reinforcing material is hydroxyapatite nanoparticles; and the processing aid includes polyethylene glycol and hydrogenated castor oil in a mass ratio of 2:1.

[0157] Degradable glass fiber is made by the following method:

[0158] A1. Add 40 parts by weight of silicon dioxide, 20 parts by weight of calcium carbonate, 5 parts by weight of calcium oxide, 5 parts by weight of calcium phosphate, 5 parts by weight of magnesium oxide and 5 parts by weight of boron oxide into a ball mill, and mix them evenly by ball milling to obtain a mixed powder;

[0159] A2. Place the mixed powder in a high temperature furnace, heat until completely melted, and keep the temperature for 3 hours to obtain a uniform glass melt;

[0160] A3, drawing the glass melt through a glass fiber drawing machine, controlling the drawing temperature to be 1000°C and the drawing speed to be 300m / min, placing the drawn fiber in an annealing furnace at 400°C for 3h, and cooling to obtain a glass fiber with a diameter of 3μm;

[0161] A4. Coat the polymer solution on the surface of the glass fiber with a coating thickness of 2 μm. Dry at 50° C. for 3 h and cut to obtain 300 tex degradable glass fiber.

[0162] The polymer solution was prepared by the following method:

[0163] Caprolactone monomer, vanillic acid, syringic acid and stannous isooctanoate in a mass ratio of 10:1:1:0.1 were added to chloroform, and after being fully mixed, the reaction system was heated to 100° C. under nitrogen protection and polymerized for 8 hours to obtain a polymer solution.

[0164] A method for preparing a glass fiber reinforced high-viscosity medical composite material comprises the following steps:

[0165] S1. Weigh the base polymer, degradable glass fiber, reinforcing material and processing aid according to weight for later use;

[0166] S2, blending the base polymer, the reinforcing material and the processing aid uniformly by a high-speed mixer to obtain a mixture;

[0167] S3. Add the mixture into an extruder at 150°C through a feeder with a feeding frequency of 3Hz and a feeding speed of 40rpm. After the melt is extruded out of the die, add degradable glass fiber at the fiber adding port, adjust the main engine speed to 240r / min, extrude and granulate, and obtain the required glass fiber reinforced high-viscosity medical composite material.

[0168] Performance Testing

[0169] The properties of the glass fiber reinforced high viscosity medical composite materials in Examples 1-3 of the present invention and Comparative Examples 1-5 were tested respectively, as follows:

[0170] According to the national standard GB / T 1040.1-2018 "Determination of tensile properties of plastics", the tensile strength and elongation at break were measured;

[0171] The bending strength was measured according to the national standard GB / T 9341-2008 "Determination of flexural properties of plastics";

[0172] The heat deformation temperature was measured according to the national standard GB / T 1634.1-2019 "Determination of load deformation temperature of plastics";

[0173] The intrinsic viscosity of the mixture before and after extrusion by the extruder was measured by using a VISCO-370 viscometer. The intrinsic viscosity of the mixture before extrusion by the extruder was subtracted from the intrinsic viscosity of the mixture after extrusion by the extruder to obtain the intrinsic viscosity reduction value.

[0174] The results are shown in Table 1 below.

[0175] Table 1:

[0176]

[0177] Combined with the data shown in Table 1 above, it can be seen that the comprehensive performance of the glass fiber reinforced high-viscosity medical composite materials prepared in Examples 1-3 of the present invention is significantly better than that of Comparative Examples 1-5. The glass fiber reinforced high-viscosity medical composite materials prepared in the embodiments of the present invention have excellent mechanical properties and thermal stability, can maintain a high viscosity and molecular weight during thermal processing, ensure the degradation cycle and mechanical properties in the human body are stable, and have broad application prospects.

[0178] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A glass fiber reinforced high viscosity medical composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of matrix polymer, 10-20 parts of degradable glass fiber, 6-10 parts of reinforcing material and 2-5 parts of processing aid.

2. The glass fiber reinforced high-viscosity medical composite material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of matrix polymer, 15 parts of degradable glass fiber, 8 parts of reinforcing material and 3.5 parts of processing aid.

3. The glass fiber reinforced high viscosity medical composite material according to claim 1, characterized in that: The matrix polymer includes polylactic acid, polyglycolic acid and polybutylene succinate in a mass ratio of 4-5:2-3:

1.

4. The glass fiber reinforced high-viscosity medical composite material according to claim 1, characterized in that: The degradable glass fiber is prepared by the following method: A1. Add silicon dioxide, calcium carbonate, calcium oxide, calcium phosphate, magnesium oxide and boron oxide into a ball mill, and mix them evenly to obtain a mixed powder; A2. Place the mixed powder in a high temperature furnace, heat until completely melted, and keep the temperature to obtain a uniform glass melt; A3, drawing the glass melt through a glass fiber drawing machine, annealing the drawn fiber filaments and then cooling them to obtain glass fiber filaments; A4. Coat the polymer solution onto the surface of the glass fiber, dry it, and cut it to obtain the degradable glass fiber.

5. The glass fiber reinforced high-viscosity medical composite material according to claim 4, characterized in that: The weight parts of the raw materials in step A1 are as follows: 40-50 weight parts of silicon dioxide, 20-30 weight parts of calcium carbonate, 5-15 weight parts of calcium oxide, 5-10 weight parts of calcium phosphate, 5-10 weight parts of magnesium oxide, and 5-10 weight parts of boron oxide.

6. The glass fiber reinforced high-viscosity medical composite material according to claim 4, characterized in that: The polymer solution in step A4 is prepared by the following method: Caprolactone monomer, vanillic acid, syringic acid and catalyst in a mass ratio of 10-15:1-2:1:0.1-0.3 are added to chloroform, and after being fully mixed, the reaction system is heated to 100-140° C. under nitrogen protection, and the polymerization reaction is carried out for 4-8 hours to obtain a polymer solution.

7. The glass fiber reinforced high viscosity medical composite material according to claim 1, characterized in that: The reinforcing material is hydroxyapatite nanoparticles.

8. The glass fiber reinforced high-viscosity medical composite material according to claim 1, characterized in that: The processing aid comprises polyethylene glycol and hydrogenated castor oil in a mass ratio of 2-5:1-3.

9. A method for preparing the glass fiber reinforced high-viscosity medical composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Weigh the base polymer, degradable glass fiber, reinforcing material and processing aid according to weight for later use; S2, blending the base polymer, the reinforcing material and the processing aid uniformly by a high-speed mixer to obtain a mixture; S3. Add the mixed material into the extruder through a feeder. After the melt is extruded through the die, add degradable glass fiber at the fiber adding port. At the same time, introduce a special screw component combination, extrude and granulate, and obtain the required glass fiber reinforced high-viscosity medical composite material.

10. The method for preparing the glass fiber reinforced high-viscosity medical composite material according to claim 9, characterized in that: In the special thread element combination in step S3, the element types are: ZME, chamfer, rotor, hexagonal prism, slotted element, TKR, TKL, ordinary three-head, eccentric three-head, ordinary four-head, and four-prism.

Citation Information

Patent Citations

  • A granulation processing method for biodegradable materials and the molded body prepared therefrom

    CN115157478B

  • A method for granulation and molding of polyhydroxy fatty acid esters and the granulated body thereof

    CN116277593B